Sobrevivir a la Inquisición: el proceso de Diego de Alba (1497-1498). Surviving the Inquisition: The Trial of Diego de Alba (1497-1498) - Rábade Obradó, María del Pilar (En la España Medieval, 2006)
The Inquisitorial trial of bachelor Diego de Alba, chief magistrate of Cuellar, in 1498, after proceedings begun ten years earlier and based on accusations of judiazing, which were proven false in the trial. Considerations regarding local hostility toward outstanding conversos, as in this case.